2019
DOI: 10.29252/jss.13.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gaussian Spatial Models with Covariate Measurement Error

Abstract: Uncertainty is an inherent characteristic of biological and geospatial data which is almost made by measurement error in the observed values of the quantity of interest. Ignoring measurement error can lead to biased estimates and inflated variances and so an inappropriate inference. In this paper, the Gaussian spatial model is fitted based on covariate measurement error. For this purpose, we adopt the Bayesian approach and utilize the Markov chain Monte Carlo algorithms and data augmentations to carry out calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[3]'s simulation revealed better performance of MCEM approach compared to naive approach measurement error model. [4] using Bayesian approach analyzed Gaussian spatial model with covariate measurement error under an exponential spatial structure. Unlike [1], [4] consider the functional model, i.e., a fixed true values of covariate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3]'s simulation revealed better performance of MCEM approach compared to naive approach measurement error model. [4] using Bayesian approach analyzed Gaussian spatial model with covariate measurement error under an exponential spatial structure. Unlike [1], [4] consider the functional model, i.e., a fixed true values of covariate.…”
Section: Introductionmentioning
confidence: 99%
“…[4] using Bayesian approach analyzed Gaussian spatial model with covariate measurement error under an exponential spatial structure. Unlike [1], [4] consider the functional model, i.e., a fixed true values of covariate. The simulation found that the proposed measurement error model has a better performance than naive model.…”
Section: Introductionmentioning
confidence: 99%